2020
DOI: 10.1182/blood-2020-136907
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Newly Diagnosed Transplant-Eligible Multiple Myeloma Patients in the Randomized Forte Trial

Abstract: Background. Proteasome inhibitor (PI)-based induction/consolidation proved to be effective in newly diagnosed multiple myeloma (NDMM) patients (pts) eligible for melphalan 200 mg/m2 plus autologous stem-cell transplantation (MEL200-ASCT). High response rates have been reported with carfilzomib (K) plus lenalidomide-dexamethasone (KRd) or cyclophosphamide-dexamethasone (KCd). Lenalidomide (R) alone is a standard of care for post-ASCT maintenance; K maintenance showed promising results in phase I/II studies, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 0 publications
0
58
0
Order By: Relevance
“…Recently, the preliminary results from the maintenance portion of the randomized phase II FORTE study were presented [ 25 ]. This study included a second randomization that occurred post-consolidation.…”
Section: Combination Therapy Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the preliminary results from the maintenance portion of the randomized phase II FORTE study were presented [ 25 ]. This study included a second randomization that occurred post-consolidation.…”
Section: Combination Therapy Strategiesmentioning
confidence: 99%
“…In both arms, lenalidomide was dosed at 10 mg/day days 1–21 of the 28-day cycle. An improvement in PFS (from second randomization) was seen in the KR arm compared to the R arm with the 30-month PFS rate of 81% (KR) vs. 68% (R) ( p = 0.0026) [ 25 ]. A higher rate of conversion to MRD negativity was observed in the KR arm (46% vs. 32%), but a higher rate of nonhematological AEs was also reported in the KR arm (27% vs. 15%, grade 3 or higher).…”
Section: Combination Therapy Strategiesmentioning
confidence: 99%
“…Novel, combination maintenance strategies are also actively being investigated. Recent updates from the FORTE trial specifically examining patients with respect to maintenance strategy demonstrated an improved 3-year PFS with carfilzomib and lenalidomide maintenance rather than lenalidomide alone (75% vs 66%, HR 0.63; p=0.026) [44] Patients in the carfilzomib and lenalidomide maintenance group had higher rates of transition from MRD-positive to MRD-negative during maintenance (46% vs 32%, p=0.04) [44]. The superiority of "double" maintenance in high-risk patients is of particular interest since many Canadian myeloma experts are already recommending a combination of lenalidomide plus a proteasome inhibitor (bortezomib or ixazomib) as maintenance in such patients.…”
Section: Distinction Between Treatment Vs Maintenance Doses Of Lenalimentioning
confidence: 99%
“…The phase 3 FORTE trial tested the role of autologous stem cell transplant (ASCT) in 315 newly diagnosed patients who were randomized to receive either carfilzomib, lenalidomide and dexamethasone (KRd) plus ASCT or KRd alone for 12 months (KRd-12mo). At a median follow-up of 45 months, the median PFS was not yet reached for KRd-ASCT vs 57 months for KRd-12mo (HR 0.64, p = 0.023) [ 52 ]. This FORTE trial confirmed that KRd-ASCT significantly improved PFS when compared with KRd-12mo.…”
Section: Introductionmentioning
confidence: 99%